MPLS next steps - Davie, Bruce S.; Farrel, Adrian (Amsterdam ; Boston : Elsevier/Morgan Kaufmann Publishers, 2008)
SHORT DESCRIPTION: Multiprotocol Label Switching (MPLS) is a data plane and control technology that is used in packet (that is Internet Protocol) networks. Now over ten years old, it has taken root firmly as a fundamental tool in many service provider networks. The last ten years have seen a considerable consolidation of MPLS techniques and protocols. This has resulted in the abandoning of some of the original features of MPLS, and the development of other new features. MPLS has moved from a prospective solution, to a grown-up technology. Now that MPLS has reached this level of maturity, these new tools and features allow more sophisticated services to the users of the network. These tools and features are discussed within various contexts throughout several networking-related books published by MK and this presents us with a unique publishing opportunity. The proposed book is a best-of-the-best collection of existing content from several books MK has published in recent years on MPLS technology (multi-label protocol switching). Individual chapters on MPLS technology are derived from a handful of MK books and are combined in one new volume in a way that makes sense as a reference work for those interested in new and developing aspects of this technology, i.e., network operators and designers who need to determine which aspects of their networks would benefit from MPLS technology and applications. It also serves as a definitive reference for engineers implementing MPLS-based products. This book represents a quick and efficient way to bring valuable content together from leading experts in the field while creating a one-stop-shopping opportunity for customers to receive the information they would otherwise need to round up from separate sources. Suitable and current content will be collected from the following titles: Evans, Deploying IP and MPLS QoS (2006); Farrel, GMPLS (2005); Ash, Traffic Engineering (2006); Vasseur, Network Recovery (2005); Farrel, The Internet and Its Protocols (2004); Nadeau, MPLS Management (2003); and Davie, MPLS Technology and Applications (2000). These chapters will be updated where necessary and two new chapters will be added at the beginning and the end of the book to bring the content into focus and discuss next generation developments. * Coverage of major applications of MPLS such as traffic engineering, VPNs, IP integration, GMPLS, and QoS written by leading experts in the field contributes to your practical knowledge of this key technology * Shows you how to implement various MPLS applications that will result in saving your organization time and money * Shows you how you can evaluate MPLS applications and techniques in relation to one another so you can develop an optimum network design.
Ch 1 Fundamental Concepts of MPLS Technology (NEW) -- Ch 2 MPLS to GMPLS (reprint Ch 3 of Farrel/Bryskin, GMPLS) -- Ch 3 MPLS Traffic Engineering and QoS (reprint Ch 3 of Ash, TE and QoS) -- Ch 4 GMPLS Traffic Engineering (reprint Ch 8 of Farrel/Bryskin -- Ch 5 MPLS Traffic Engg and Recovery (reprint Ch 8 of Vasseur, Netwk Recovery) -- Ch 6 GMPLS and Service Recovery (reprint Ch 7 fromFarrel/Bryskin)- 65pp -- Ch 7 MPLS Traffic Engineering Mngmt (reprint Ch 8 from Nadeau, MPLS Mngmt) -- Ch 8 MPLS Fast Reroute (NEW).
Includes index.
Keywords: MPLS standard; Electronic books